Natural convection flow on a sphere through porous medium in presence of heat source/sink near a stagnation point - Mukhopadhyay, Sourangshu (Mathematical Modelling and Analysis, 2008)
Steady natural convection boundary‐layer flow in the neighbourhood of lower stagnation point of a heated sphere embedded in a saturated porous medium in presence of heat source/sink is considered. The dimensionless governing equations for this investigation are solved numerically by shooting method. Then attention is focused on finding the effects of porosity parameter, heat source/sink parameter and the Prandtl number on velocity and temperature distributions. With the increase of permeability parameter of the porous medium, the fluid velocity decreases but the temperature increases at a particular point of the surface. Due to increasing values of heat source/sink parameter, fluid velocity is found to increase. It is noticed that the velocity boundary layer is suppressed with the increasing Prandtl number and the temperature decreases in this case. Prandtl number has an important effect in increasing the rate of heat transfer from the surface of the sphere.First Published Online: 14 Oct 2010